IKEA and Wal-Mart: Comparison of Transferable Factory Specific Advantages (FSAs) in Internationalization (International Journal of Scientific Research and Management (IJSRM), 2021)
This study investigates the cases of two mega size retailers, IKEA and Wal-Mart and their internationalization approaches. Whereas IKEA is a Sweden based company that started in 1934 and expanded to 52 countries by 2021 with 378 stores, Wal-Mart is US based company started in 1962 and expanded throughout 26 countries by 2021 with 11,443 stores.